Fracture Strength of Monolithic Zirconia Crowns with Modified Vertical Preparation: A Comparative In Vitro Study - Abdulazeez, Marwah Ismael; Majeed, Manhal A. (European Journal of Dentistry, 2021)
Objective The aim of this study was to evaluate the influence of different marginal designs (deep chamfer, vertical, and modified vertical with reverse shoulder) on the fracture strength and failure modes of monolithic zirconia crowns.Materials and Methods Thirty sound human maxillary first premolar teeth with comparable size were used in this study. The teeth were divided randomly into three groups according to the preparation design (n = 10): (1) group A: teeth prepared with a deep chamfer finish line; (2) group B: teeth prepared with vertical preparation; and (3) group C: teeth prepared with modified vertical preparation, where a reverse shoulder of 1 mm was placed on the buccal surface at the junction of middle and occlusal thirds. All samples were scanned by using an intraoral scanner (CEREC Omnicam, Sirona, Germany), and then the crowns were designed by using Sirona InLab 20.0 software and milled with a 5-axis machine. Each crown was then cemented on its respective tooth with self-adhesive resin cement by using a custom-made cementation device. A single load to failure test was used to assess the fracture load of each crown by using a computerized universal testing machine that automatically recorded the fracture load of each sample in Newton (N).Statistical Analysis The data were analyzed statistically by using one-way analysis of variance test and Bonferroni test at a level of significance of 0.05.Results The highest mean of fracture load was recorded by chamfer (2,969.8 N), which followed by modified vertical (2,899.3 N) and the lowest mean of fracture load was recorded by vertical (2,717.9 N). One-way ANOVA test revealed a significant difference among the three groups. Bonferroni test showed a significant difference between group A and group B, while a nonsignificant difference was revealed between group C with group A and group B.Conclusion Within the limitations of this in vitro study, the mean values of fracture strength of monolithic zirconia crowns of all groups were higher than the maximum occlusal forces in the premolar region. The modification of the vertical preparation with a reverse shoulder placed at the buccal surface improved the fracture strength up to the point that it was statistically nonsignificant with the chamfer group.
Keywords: zirconia; vertical; reverse shoulder